Online Single Submission Risk Based Approach Policy (OSS RBA) for Micro Small Business Development Intermediate - Alip Rahman (PT Publikasiku Academic Solution, 2023)
Regional developments in global competition have demanded efforts to increase competitiveness through avoiding the occurrence of a high cost economy that has been complained about so far, due to the slow government bureaucracy which always demands greater costs than the service bureaucracy itself, for example through licensing facilities, to create efficiency for optimal resource utilization, in the context of building the birth of a perfect market mechanism. Market failure can be avoided by formulating licensing norms. Increasing regional competitiveness and absorption of regional income in the investment sector through the implementation of the Online Single Submission Risk Based Approach (OSS RBA) System Policy for Micro, Small and Medium Enterprises (MSMEs), for this reason, every business activity has a direct impact on modifying the policy format model, including institutional structure, and related to business service platforms, for the Central and Regional Governments. At the level of local policies, this is not an easy problem, in an effort to accommodate these interests, in the era of global competition. The effectiveness of the implementation of the RBA OSS System Policy by Regional Governments, as well as how to overcome obstacles to the policy are very interesting to analyze, regarding MSME Actors who experience limited conditions, in terms of capital, mastery of technology and market share. The method used to analyze is doctrinal (normative juridical), on the approach of the concept of law as written law in the form of statutory texts, which are built by local government regulations. The research findings state that the Regional Government, that Micro, Small and Medium Enterprises still need assistance to register permits, in terms of the RBA OSS System Policy in the mission of optimizing the policy, massive socialization must be carried out to the community, especially MSME actors, to increase information on the importance of this policy. In the end, the business actors in question no longer make mistakes in relation to determining the choice of categorization of Micro Small and Non-Small Micro Enterprises. This policy model is directly very influential in efforts to improve the efficiency of public services, and avoid the high cost economy that occurs.